Private Environmental Governance in the Ethiopian Pesticide Supply Chain: Importation, Distribution and Use. (1st March 2016) - Mengistie, Belay T.; Mol, Arthur P.J.; Oosterveer, Peter
Highlights: The pesticide distribution system in Ethiopia is vulnerable to environmental and health risks. The Ethiopian government has been unsuccessful to regulate the pesticide market, as is manifested in a lack of monitoring and surveillance. A tracking and tracing system on the sales and use of pesticides is needed. Involvement of private actors in Ethiopian pesticide governance may be an important gap-filler of state inefficiencies to some of the most intractable environmental problems. Internal company-based environmental management systems alone are insufficient for effective sustainability governance of pesticide supply chains and coordination among chain actors is essential. Abstract: Agricultural pesticides are important chemicals that are used to mitigate crop damage or loss and improve productivity. However, pesticides may cause negative environmental and human health effects depending on their specific distribution and use. Securing environmental safety and sustainability of pesticide distribution and use is widely seen as an important challenge for pesticide governance. This paper analyses how, why and under what circumstances Ethiopian pesticide supply chain actors deal with (un)safe distribution and use of pesticides and assesses their potential contribution to securing the quality, environmental safety and sustainability of pesticides importation, distribution and use. The framework developed for this is based on sustainable supply chain governance in order to assess the roles of and the interactions between the different chain actors, supporters and influencers . On the basis of field research in Ethiopia among key chain actors (importers, retailers, farmers) we analyse their involvement in three different environmental governance mechanisms: governing material flows of pesticides, managing information on health and environmental safety and providing training and capacity-building services . The study found the organisation of the pesticides supply chain in Ethiopia as atomistic. Environment and health hardly played a role in pesticides handling by the different supply chain actors, which was dominated by immediate profit motives. As a consequence smallholder farmers are put at risk because they are refrained from training, support or information provision on pesticides. Indeed, it was a failure of state governance that led importers and retailers to aggressive marketing and distributing pesticides unsafely and hinder the proliferate of private mode of governance. At the same time, a small signs of hope have also been identified at the supporters' and influencers' side of the chain. Successful environmental supply chain governance for safe pesticide distribution and use requires coordination and as well as training and information sharing (interaction) among pesticide supply chain actors, supporters and influencers at all levels-local, national and global as elements of one system of governance. Finally, the evidence presented in this paper suggests that due to limits in governmental capacity and concerns on commercial viability and on social and environmental impacts among private actors, there will be a role for private actors alongside public actors to ensure safe pesticide distribution and use. Public-private partnerships might constitute an attractive strategy for this aim.